Revamping Business Education Needs to Meet 21st Century Reality the Future of Business Education in Nigeria - Daniel Iyoha; Ugonwa Felicia Umeh; Zorte Nbogana Maamaa (International Journal of Education, Teaching, and Social Sciences, 2023)
Since 21st century began over two decades ago, there seems to be a paradigm shift in educational values across the globe. This has left us with the options of either to swim or sink. In order not to sink, educational systems of most countries of   the world began to rethink educational practices in order to remain relevant in this knowledge economy and communication technology driven age. Up to the advent of the twenty-first century, education systems around the world concentrated on training their students to simply acquire content and knowledge. Students were therefore seen as needing to learn reading and numerical skills in order to acquire content and information. But more recently, information and knowledge have become widely available and simple to obtain because of advances in technology and communication. Business education has been thought to be an instructional model that instills in its client the necessary applicable skills, talents, and competencies for independence. Even though these abilities are still vital and relevant, but are no more enough to keep degree holders employed in the volatile and competitive economy. As a result, there is a massive disparity between the information and expertise that students gain in university and those that they would need succeed in quintessential 21st century cultures and organizations. It is necessary to modify toward offering learners a set of abilities that depended not just on intellect but on all interrelatedness of mental, behavioral, and affective traits if we are to react appropriately to these contemporary innovation, target audience, and cultural transformations. In considering this, the paper examined the concepts of 21st century education, 21st century learning objectives, the concept of business education, and the communication technological skills in 21st century required of graduates. Also, conclusions and key recommendations were offered.